The Effects of Oil Shocks on Turkish Macroeconomic Aggregates - Al Rasasi, Moayad; Yilmaz, Mustafa (International Journal of Energy Economics and Policy, 2016)
This paper examines the impacts of oil price shocks on macroeconomic aggregates of Turkey. We find evidence suggesting the influential role of oil price shocks on macroeconomic aggregates. In other words, we find that oil price shocks affect output growth negatively with a delay. However, higher oil prices are associated with higher inflation, and depreciating exchange rate. We also explore the role of asymmetric oil shocks on macroeconomic aggregates and find that both oil price increases and decreases are associated with a delayed lower output growth rate. Furthermore, we find oil price increases affect inflation positively a delay. The appreciation of exchange rate appears with a delay due to oil price decreases. Keywords: Oil Price Shocks, Economic Activity, Turkey JEL Classification: C22, C32, Q43